Permainan Game Online Berbasis Perjudian dalam Perspekif Hukum Pidana: Gaming Based Online Games in Criminal Law Perspective - Yusuf Hanafi Pasaribu (DOKTRINA: JOURNAL OF LAW, 2022)
This paper will describe online games with the dimension of gambling, so that the discussion is about the form of online games with the dimensions of online gambling in the aspect of criminal law and the application of criminal sanctions for users of online games with the dimensions of online gambling from the perspective of criminal law. The research method uses normative juridical research which refers to secondary data that reveals data that takes the truth obtained from the literature and the field by combining regulations, scientific books that are related to this research. The results of the study found that the form of online games with the dimensions of online gambling in the aspect of criminal law that online games with dimensions of online gambling through the internet network is a form of gambling in which the entire process is both the stakes, the games and the collection of money via the internet which of course the players have to do. an upfront deposit before being able to play online gambling games. Forms of online gambling games found on internet networking sites, for example chips game higgs domino, sports gambling, texas holdem poker and casino gambling games. While the application of criminal sanctions for users of online game games with the dimension of online gambling from a criminal law perspective, of course, still refers to the provisions of Article 303 of the Criminal Code and Article 303 bis of the Criminal Code and Law No. 11 of 2008 concerning Information and Electronic Transactions as amended by Law no. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions.